Paclitaxel and carboplatin chemotherapy after platinum-based chemotherapy and pembrolizumab for metastatic urothelial carcinoma - Furubayashi, Nobuki (Mol Clin Oncol, 2021)
Pembrolizumab has been available for the treatment of radical resectable urothelial carcinoma (UC) when it is exacerbated after chemotherapy since December 2017 in Japan. However, the efficacy of chemotherapy for cases progressing after pembrolizumab is unclear. The present study compared the outcomes and toxicities in patients with metastatic UC after failure of platinum-based chemotherapy and pembrolizumab, who were selected to receive paclitaxel and carboplatin (TC) chemotherapy, with those in patients who received the best supportive care (BSC). A total of 36 patients received pembrolizumab for metastatic UC at four institutions between January 2018 and August 2019. Of the 21 patients who progressed after pembrolizumab, 7 received TC chemotherapy (TC group) and 14 selected BSC (BSC group). The median observation period was 4.1 months. The 7 aforementioned patients who received TC chemotherapy (4 male and 3 female; median age, 62 years; range, 57-79 years) were analyzed in the present study. The ECOG performance status was 0 in three patients, 1 in one patient, 2 in two patients and 3 in one patient. Two patients had upper urinary tract UC, two had bladder UC and three had both types of UC. Six patients had visceral metastasis. The number of chemotherapy regimens before pembrolizumab was one in four patients, two in two patients and three in one patient. The objective response rate was 28.6% (partial response, 2 patients; stable disease, 4 patients; progressive disease, 1 patient), the median progression-free survival time was 3.4 months and the median overall survival time was 10.9 months (vs. 2.7 months in BSC group; P=0.0156). Although grade ≥3 adverse events developed in five patients, there were no treatment-associated deaths. The present results suggested that TC chemotherapy may be a preferred option for patients who require aggressive treatment after the failure of platinum-based chemotherapy and pembrolizumab.